Determination of the reactive component if fly ashes for geopolymer production using XRF and XRD - Williams, Ross; Van Riessen, Arie (Elsevier Science Ltd, 2010)
Geopolymers are a class of versatile materials that have the potential for utilisation as a cement replacement, fireproof barriers, materials for high temperatures, and biological implant applications. This study investigated methods for determining the formulation for manufacturing geopolymers made with fly ash from coal-fired power stations. The accepted method of determining the formulation of geopolymers to get the desired matrix chemistry uses the bulk composition of the feedstock materials. This formulation method is widely used in investigations using feedstock materials that almost completely react during processing. It is widely considered that amorphous components of fly ash are the reactive components in the geopolymerisation reaction. However, quantification of the amorphous components is challenging and generally avoided with the concomitant problem that the formulation is far from optimum.For the work presented here, the composition of the amorphous part is determined accurately and this information utilised to synthesise geopolymers. The bulk composition is first determined using X-ray fluorescence spectroscopy (XRF) and then the amorphous composition determined using XRF and quantitative X-ray diffraction (QXRD). Formulating the mixture based on amorphous composition produced samples with a significantly higher compressive strength than those formulated using the bulk composition. Using the amorphous composition of fly ash produced geopolymers with similar physical properties to that of metakaolin geopolymers with the same targeted composition. We demonstrated a new quantitative formulation method that is superior to the accepted method.